European Energy Law: Market System for Electricity and Gas – Energy Supply Security – Green Energy System of the Future (Green Smart Grid) - Pirstner-Ebner, Renate (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
This book deals with the European Union energy law. It contains an introduction (terms, overview), the market system for electricity and gas (e.g. equal treatment, network access), the regulatory institutions (ACER, requirements for the national regulatory authorities) and the European coordination institutions (ENTSO for Electricity etc). A separate chapter is dedicated to the security of supply for electricity and gas (risk-preparedness plan [electricity], emergency plan and solidarity principle [gas]). In addition the book deals with renewable energies, energy efficiency, storage, decentralisation (energy communities) and digitalisation (Smart Meters). It closes with the chapter “Energy System of the Future” (Green Smart Grid).